Novel Dithiolane-Based Ligands Combining Sigma and NMDA Receptor Interactions as Potential Neuroprotective Agents - Franchini, Silvia (ACS Med Chem Lett, 2020)
[Image: see text] Sigma receptors (SRs) are recognized as valuable targets for the treatment of neurodegenerative disorders. A series of novel SRs ligands were designed by combining key pharmacophoric amines (i.e., benzylpiperidine or benzylpiperazine) with new 1,3-dithiolane-based heterocycles and their bioisosters. The new compounds exhibited a low nanomolar affinity for sigma-1 and sigma-2 receptors. Five selected compounds were evaluated for their neuroprotective capacity on SH-SY5Y neuroblastoma cell line. They were able to counteract the neurotoxicity induced by rotenone, oligomycin and NMDA. Competition studies with PB212, a S1R antagonist, confirmed the involvement of S1R in neuroprotection from the oxidative stress induced by rotenone. Electrophysiological experiments performed on cortical neurons in culture highlighted the compounds ability to reduce NMDA-evoked currents, suggesting a negative allosteric modulator activity toward the NMDA receptor. Altogether these results qualify our novel dithiolane derivatives as potential agents for fighting neurodegeneration.